How do the supervisors of guidance and counseling fare in terms of accountability and performance? - Rima Pratiwi Fadli; Neviyarni Neviyarni; Riska Ahmad (Indonesian Institute for Counseling, Education and Theraphy, 2022)
Counselors, who are trained professionals, guide counselees through the process of guidance. School counselors conduct assessments as part of their services. Without an assessment, it would be impossible for us to determine whether the intended guidance program had been implemented successfully. The evaluation of the guidance program is to determine the degree to which the program's implementation has met its stated objectives. In other words, the outcome of the assessment activities will determine whether the program is successful in reaching its objectives. It cannot be isolated from the supervision actions, according to the assessment that was done. Counseling and direction School supervisors are school supervisors with complete rights, powers, and responsibilities for evaluating, promoting, and implementing education in various schools through guidance and counseling activities. Additionally, the adequacy of the services rendered by the BK teacher/counselor is determined by the factors mentioned above. This indicates that the school counselor can account for the services rendered.